Factors influencing food waste during lunch of fourth-grade school children. (15th July 2020) - Liz Martins, Margarida; Rodrigues, Sara S.P.; Cunha, Luís M.; Rocha, Ada
Highlights: Food waste on school lunch is affected by individual, social and environmental factors. The presence of teachers during the meal period is associated with low plate waste. Mid-morning snacks influence food waste at the school canteen. Meals sensory characteristics satisfaction influences food waste at the school canteen. Abstract: This study aims to explore the factors that influence plate waste at lunches served in primary schools. Data was collected for all fourth-grade children attending 21 primary schools from the city of Porto (Portugal) (n = 463). Plate waste was evaluated by the weighing method and factors influencing plate waste were collected by observation of menu and canteen characteristics and through the application of a questionnaire to children aiming to evaluate factors related to preferences and dietary patterns. Logistic regression was performed to identify predictors of plate waste. It was observed that fish menus and composed dishes showed a higher tendency for increased plate waste. However, this effect was not observed when adjusted for other variables. Soups without pulses and blended soups were less likely to be discarded by children. The presence of the teacher during meals and the possibility for children to leave the canteen whenever they wish, protected both the main dish and the soup from being wasted. A higher number of children in the canteen was associated with increased soup waste. As expected, children more pleased with the sensory characteristics of the main dish and soup were less likely to waste food. Children who consumed high-saturated fat content mid-morning snacks were more likely to waste soup. The main factors associated with plate waste were related to the presence of teachers during the mealtime, school meal policies and the meals' sensory characteristics. Additionally, soup waste was determined by its composition, mid-morning snacks and the number of children in the canteen.